Ijtihad-ijtihad (Interpretasi) Kebahasaan Tammam Hassan - Raswan (Universitas Negeri Jakarta, 2015)
In this article the writer proposes ijtihad-ijtihad Tammam Hassan in the study of nahwu (Arabic grammatical). And ijtihadat lughawiyyah books which is his masterpiece is the climax of ijtihad that have been initiated since long. Among the results of ijtihad are the first, the view that science of nahwu should always be assessed and investigated, because the language had been developed, the study raised should not stop as long as there is progress in the language besides research methods must be reformulated. Second, the view that the Arabic sentences should pay attention to the elements of al-rashf, if not then an Arabic expression would be very difficult to be understood. The more disciplined in following this rule 'rashf' then the sentence will be more easily understood by the reading and listening public. Third, the view that the core purposes of make arrangement 'mabna' meaning is to succeed. in other words the rule 'mabna' could be violated if the meaning is not violated or not be ambiguous/unambiguous.